2018
DOI: 10.1002/app.46365
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane‐incorporated chitosan/alginate core–shell nano‐particles for controlled oral insulin delivery

Abstract: Chitosan (CS) and polyurethane-chitosan (PU-CS) nano-particles (NPs) were prepared for the core formation by complex coacervation method whereas alginate (ALG) and PU-ALG were crosslinked by ionic gelation method to form the protective shelllayer over the core. Effects of PU incorporation either within the core or shell or both were investigated by different in vitro and in vivo parameters. Fourier transform infrared (FTIR) spectroscopy of different compositions of nano-particles showed distinct characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Logically, the slightly faster protein release from nanoparticles can be attributed to the higher surface area in the nanoscale, leading to increased interaction with dissolution media and enhancing water permeation. Some studies have reported drug release (i.e., insulin and naringenin) from core–shell chitosan-alginate particles, indicating the sensitivity of the core–shell to the pH of media for oral delivery application 22 , 24 . In contrast, the sequential sustained drug release from core–shell particles was just investigated in physiological pH for tissue engineering purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Logically, the slightly faster protein release from nanoparticles can be attributed to the higher surface area in the nanoscale, leading to increased interaction with dissolution media and enhancing water permeation. Some studies have reported drug release (i.e., insulin and naringenin) from core–shell chitosan-alginate particles, indicating the sensitivity of the core–shell to the pH of media for oral delivery application 22 , 24 . In contrast, the sequential sustained drug release from core–shell particles was just investigated in physiological pH for tissue engineering purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that polymeric nanoparticle presented satisfactory safety profile and negligible toxicity [8,53,99,100]. For instance, the lyophilized insulin-loaded modified chitosan nanoparticles did not show any toxicity in GI cells after being treated for 3 h [8].…”
Section: Cytotoxic Effect Of Insulin-loaded Nanoparticlesmentioning
confidence: 91%
“…For instance, the encapsulation of probiotic Lactobacillus acidophilus into alginate and chitosan‐alginate microspheres resulted in not only a slightly better mucoadhesion rate, but also in a 1.7× improved survival rate of the encapsulated probiotic compared to the free Lactobacillus acidophilus after 2 h exposure to simulated gastric fluid 50. In an another study, Bhattacharyya et al51 showed that 86–91% of polyurethane‐modified chitosan and alginate nanoparticles were found to adhere to mouse intestines after 30 min washing with continuous buffer flow. Furthermore, ≈10% insulin bioavailability in mice after oral administration was found when using these particles as carriers.…”
Section: Mucoadhesionmentioning
confidence: 99%